The Acquisition of French as a Second Language - Howard, Martin (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Focusing on French, this collection of articles spans different facets of second language acquisition research, including different areas of a learner's language system in French such as the development of verbal, nominal, and adjectival morphology. Other articles explore input matters relating to the learner's language exposure as well as the role of individual factors in the learner's developmental trajectory. The studies presented offer insight into contemporary developments in relation to the investigation of both well-established and newer emerging themes and issues in second language acquisition research and showcase the contributions of French in such work. They draw on different approaches and methods to offer an exploration of contemporary areas of focus in French second language acquisition among learners of different source languages, at different levels of development, and in different learning contexts.